Theoretical Study on the Inhibition Mechanism of the Proteasome by Bortezomib (Communications in Computational Chemistry, 2025)
Bortezomib can form covalent bonds with the proteasome to kill myeloma tumor cell, but the detailed covalent inhibition reaction mechanism remains unclear. In this study, we first established the parameters for boron atom in bortezomib and explored the possible reaction pathways of inhibition of the proteasome by bortezomib through molecular dynamics (MD) simulation and Quantum Mechanics/Molecular Mechanics (QM/MM) calculation. The computational results indicate that the most energetically favorable pathway includes two reaction steps. The first step involves a proton abstraction from the -OH group to ${\rm-NH_2}$ group of Thr1 residue, which is coupled with the nucleophilic attack on the boron atom of bortezomib by the newly formed ${\rm O}^-$ ion. The second step is the proton transfer from the protonated ${\rm-NH_3^+}$ group to one of the hydroxyl group connected to the boron atom, forming a bortezomib-proteasome complex associated with a water molecule coordinated with the boron atom. The rate-determining step of the inhibition reaction is the first step with an energy barrier of 19.1 kcal/mol, which is close to the activation energy of ~20.8 kcal/mol derived from kinetic experiments. This work provides detailed mechanistic insights for proteasome inhibition by the boron compounds.
Keywords: bortezomib; proteasome; inhibition mechanism; QM/MM calculation